Pengaruh Pemberdayaan Struktural Terhadap Kepuasan Kerja Perawat Dengan Pemberdayaan Psikologis Sebagai Mediating Factor - Supriyadi; Arief Fardiansyah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Empowerment is the process of dividing power between superiors and subordinates. Nurse empowerment is one of the factors that can improve performance through job satisfaction. The purpose of this study is to determine the effect of structural empowerment on nurses' job satisfaction with psychological empowerment as a mediating factor at RA. Basoeni Hospital, Mojokerto Regency. This study uses a crossectional design Hospital. with a research sample of 130 hospital nurses who are selected in total sampling with questionnaires and then analyzed using a multivariate test with JASP software. The results of the study showed that almost all respondents perceived structural empowerment in high empowerment, namely 107 people (82.3%), almost all respondents perceived psychological empowerment in high empowerment, namely 104 people (80%) and most of the respondents stated that they were very satisfied with working at RA Basoeni Hospital, Mojokerto Regency, which was 95 people (73.1%). The results of the multivariate test showed that structural empowerment was proven to have an effect on nurses' job satisfaction (Estimate = 0.719, Z value = 9.388 and Pvalue <0.001), structural empowerment was proven to have an effect on psychological empowerment (Estimate = 0.429, Z value = 8.007 and Pvalue <0.001). Psychological empowerment was proven to have an effect on nurses' job satisfaction (Estimate = 0.638, Z value = 6.226 and Pvalue <0.001). The results of the mediation test with JASP software showed that psychological empowerment was proven to be a mediating factor between structural empowerment and nurses' job satisfaction (Pvalue <0.001). Nurses who are empowered by supportive management practices will have a high value of structural empowerment, then intrinsic motivation emerges in psychological concepts that have an impact on the emergence of job satisfaction. Therefore, supportive management is needed in the management of quality services in hospitals.